Waktu Kultivasi Optimal dan Aktivitas Antibakteri dari Ekstrak Etil Asetat Jamur Simbion Aspergillus unguis (WR8) dengan Haliclona fascigera - Agnes Rendowaty; Akmal Djamaan; Dian Handayani (Fakultas Farmasi Universitas Andalas, 2017)
The optimal cultivation time of symbiont fungi Aspergillus unguis (WR8) with marine sponge Haliclona fascigera and antibacterial activity assay from the ethyl acetate extracts symbiont fungi A. unguis (WR8) have been determined. The fungi was cultivated on Sabaoraud Dextrose Broth medium in both static condition and using shaker incubator at 120 RPM at 25-28oC. Optimal cultivation time was determined by the amount of dry biomass mycelium fungi per unit of time. Liquid medium was extracted with ethyl acetate and used for antibacterial activity assay using agar diffusion method against Staphylococcus aureus. The study showed that the optimal cultivation time of symbiont fungi A. unguis (WR8) in static condition was achieved on day 21 while the extract (5 % w/v) inhibited bacterial growth of S. aureus with an inhibition zone of 21 mm. Meanwhile, The optimal cultivation time in the shaker was achieved on day 14 and the inhibition zone of the extract was 11 mm. The study concludes that the optimal cultivation time for production of antibacterial compounds by symbiont fungi A. unguis (WR8) was obtained at 21 days in static condition.